Writing Video Script of Green Canyon to Promote Tourism Destination in Lahat - Yandi, Meisy Aisya Putri; Shahab, Aisyah; Sari, Evi Agustina (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2023)
This final report is aimed at writing video script to promote tourism destination in Lahat. The purpose of this research is to know how to write video script of Green Canyon to promote tourism destination in Lahat. In this final report the writer used Research and Development method modified by Sukmadinata (2005). This method consisted of three steps: (1) Preliminary Study, (2) Model Development, and (3) Final Product Testing. The writer collected data by conducting observation and interview as a reference to write video script and to get some information. After the video script was designed, it was checked by 3 experts. The result of this research was the writer conducted 3 steps of R&D method and 10 stages in making a video script to promote tourism destination in lahat. Keywords: Writing, Script, Video, Tourism, Green Canyon.